Testing endurance in soccer - a comparison - Zallinger, G.; Schimpl, G.; Drachta, O.; Müller, E. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The game of soccer has enormously increased in terms of physical preconditions for each of the players. Endurance has become a major goal in physical preparation for a demanding season. Estimating endurance on an economic base and professionally working out at proper heart rates is a challenge for coaches and collaborating scientists as well. Therefore the step-test on a treadmill, calculating the lactate-performance-course is a widely accepted measure to derive velocities at defined lactate-thresholds and assigned heart rates, though being very time-consuming. Other test protocols might be of advantage in terms of economy in testing, but validity of results is not always provided. Aim of this study was to compare different test protocols and proof their validity and usability. Methods We submitted a group of professional players (n=12) to three endurance tests and correlated parameters (velocity at La2, La3, La4, corresponding heart-rates and deflection points respectively). Test protocols: (1) Step test 5` on a treadmill: 9.0-16.2 kmh-1 (increment: 1.8 kmh-1) (2) Shuttle-run indoor (3`; 20m distances); 7.9, 9.7, 11.5, 13.3 kmh-1 (3) Conconi test on a treadmill (200 m/0.5 kmh-1 increments): start velocity = 9.0 kmh-1 Results Defining the step test 5` as our reference value correlations to shuttle-run-velocities at La2 and La4 were significant (r=0.93; 0.8), only the shuttle run estimated the threshold velocities 0.6 kmh-1 in both cases lower than the step test (5%; 4%). No significant correlation was found for the corresponding heart rates, as well as for all parameters of the conconi test (deflection point velocity and heart-rate). Due to overestimation of heart rate in case of the shuttle run (4 mmol/l), we also compared the 3-mmol/l- parameters to 4 mmol/l-threshold of the step test (Fig.1). As a result the significant correlation in both velocity (r=0.87) and heart rate (r=0.77) was obvious. Differences in velocities resulted in 1.77 kmh-1 (12%, n.s.). Mean values of the heart rate were 176.9 ± 5.9 min-1 (step test) and 174.8 ± 7.6 min-1 respectively. Discussion Though underestimation of endurance performance was evident, results showed that the shuttle run protocol as described can be used as test- and control-tool in professional soccer. Besides valid estimations of performance and heart rate responses the shuttle run is highly economic in case of testing soccer-teams at regular intervals throughout the season.